Reversible Stress‐Driven and Stress‐Free Two‐Way Shape Memory Effect in a Sol‐Gel Crosslinked Polycaprolactone. Issue 1 (21st October 2022) - Inverardi, Nicoletta; Pandini, Stefano; Gemmo, Gabriele; Toselli, Maurizio; Messori, Massimo; Scalet, Giulia; Auricchio, Ferdinando
Abstract: The two‐way shape memory effect is the ability of a material to change its shape between two configurations upon application and removal of a stimulus, and, among shape memory polymers, it is featured only by few systems, such as semicrystalline networks. When studied under tensile conditions, it consists of elongation–contraction cycles along cooling and heating across the crystallization and melting region, typically under the application of a constant load. However, recent studies on crosslinked semicrystalline co‐polymers demonstrate that also a completely stress‐free, or self‐sustained, two‐way effect may be achieved through specific thermomechanical cycles. This effect is currently regarded with interest for the development of intrinsically reversible sensors and actuators, and it may also be displayed by simpler materials, as homopolymer‐based semicrystalline networks. Only seldom articles investigate this possibility, therefore in this work the two‐way shape memory behavior is studied on a poly(ɛ‐caprolactone) system, crosslinked by means of a sol‐gel approach. The effect is studied both under stress‐driven and stress‐free condition, by applying properly set‐up thermo‐mechanical histories. The results allow to describe the effect as a function of temperature, to reveal the dependence on specific testing parameters and to compare the extent of the reversible strain variation under these two conditions.